2011
DOI: 10.1007/s11368-011-0388-6
|View full text |Cite
|
Sign up to set email alerts
|

Warming and grazing affect soil labile carbon and nitrogen pools differently in an alpine meadow of the Qinghai–Tibet Plateau in China

Abstract: Purpose Small but highly bioactive labile carbon (C) and nitrogen (N) pools are of great importance in controlling terrestrial C and N fluxes, whilst long-term C and N storage is determined by less labile but relatively large sizes of C and N pools. Little information is available about the effects of global warming and grazing on different forms of C and N pools in the Qinghai-Tibet Plateau of China. The aim of this study was to investigate the effects of warming and grazing on the sizes of different soil lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 73 publications
(93 reference statements)
7
71
0
Order By: Relevance
“…This is consistent with soil microorganisms showing a high level of sensitivity to variation in temperature, and displaying increasing soil temperatures throughout the typical ambient ranges (Schutt et al, 2014;Bing et al, 2016). This is in accordance with Wang et al (2014) and Rui et al (2011) who reported an increase of N-NH 4 + and microbial biomass after soil warming experiments in an alpine meadow. Also, Harrison et al (2008) reported that soil DOC concentration increased after a rise in temperature in the upland soils on the Northern Pennines, which was mainly associated with solar radiation and temperature.…”
Section: Soil N and C Forms In Relation To The Pedoclimatic Conditionsupporting
confidence: 90%
“…This is consistent with soil microorganisms showing a high level of sensitivity to variation in temperature, and displaying increasing soil temperatures throughout the typical ambient ranges (Schutt et al, 2014;Bing et al, 2016). This is in accordance with Wang et al (2014) and Rui et al (2011) who reported an increase of N-NH 4 + and microbial biomass after soil warming experiments in an alpine meadow. Also, Harrison et al (2008) reported that soil DOC concentration increased after a rise in temperature in the upland soils on the Northern Pennines, which was mainly associated with solar radiation and temperature.…”
Section: Soil N and C Forms In Relation To The Pedoclimatic Conditionsupporting
confidence: 90%
“…The warming amplitude increases with increasing altitude on this Plateau (Liu and Chen 2000;Yao et al, 2000). Field experiments have analysed the potential effects of warming on the alpine soils on the Tibetan Plateau (Fu et al, 2012;Li et al, 2011;Rui et al, 2011;Xu et al, 2010a;Yu et al, 2014). However, a synthesis of the experimental warming data is still unavailable and thus, the general tendency of the warming effects remains unclear for alpine soils across this Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the declines of GPP, AGB and ANPP under warming may be also related to changes in the soil microbial biomass because soil microbial activity may affect soil nitrogen (N) availability. Plant productivity increases with increasing soil N availability or inorganic N in alpine meadows on the Tibetan Plateau (Rui et al 2011;Zong et al 2013;Fu et al 2014;Yu et al 2014). Zong et al (2013) showed that warming significantly reduced the net N mineralization rate at low elevations.…”
Section: Resultsmentioning
confidence: 99%